Analyzing The Ability of Twelfth Grade Students in Writing Application Letter at Senior High School Number 11 jambi - Ulfa, Fenny Vadia; Wennyta, Wennyta; Dewi, Kartika (Universitas Batanghari Jambi, 2023)
The Purpose of the research is to analyzed the ability of twelfth grade students to write application letter at senior high school number 11 Jambi. In conducting the research, the researcher used descriptive quantitative. The researcher used quantitative method to analyze the data. It can be seen there are 18 students got excellent score in 80-100, 12 students got good score 66-79, 1 student got fear score in 56-65, 2 students got weak score in 46-55 and no students got poor score in 0-45. This condition showed that some of the twelfth grade of Senior High School number 11 Jambi were able to write the application letter. Because they know how to make a good application letter such as the salutation, the content, and closing.